2012
DOI: 10.3892/ol.2012.874
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA mutations in human tumor cells

Abstract: Abstract. Mitochondria play significant roles in cellular energy metabolism, free radical generation and apoptosis. The dysfunction of mitochondria is correlated with the origin and progression of tumors; thus, mutations in the mitochondrial genome that affect mitochondrial function may be one of the causal factors of tumorigenesis. Although the role of mitochondrial DNA (mtDNA) mutations in carcinogenesis has been investigated extensively by various approaches, the conclusions remain controversial to date. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Further, we conducted statistical analysis on the status of the base pairs for the point somatic mutations, except for 52 somatic mutations lacking information regarding the status of the base pairs. We found that the most frequent (52.48%) of the somatic point mutations were homoplasmic, and 45.76% were heterogenetic, which agrees with the results of a previous study (Li and Hong, 2012;Yu, 2012) and the fact that cell fission with somatic mtDNA mutations increase the number of and fix mutant types in tumor tissue (Polyak et al, 1998;Penta et al, 2001). We also found that most point mutations were transitions between pyridine and purines (12.70%; 71/559); this mutation pattern was similar to that of oxidative decay on DNA caused by ROS in normal tissues, and may explain the elevated levels of ROS during the tumor development (Beckman and Ames, 1997).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Further, we conducted statistical analysis on the status of the base pairs for the point somatic mutations, except for 52 somatic mutations lacking information regarding the status of the base pairs. We found that the most frequent (52.48%) of the somatic point mutations were homoplasmic, and 45.76% were heterogenetic, which agrees with the results of a previous study (Li and Hong, 2012;Yu, 2012) and the fact that cell fission with somatic mtDNA mutations increase the number of and fix mutant types in tumor tissue (Polyak et al, 1998;Penta et al, 2001). We also found that most point mutations were transitions between pyridine and purines (12.70%; 71/559); this mutation pattern was similar to that of oxidative decay on DNA caused by ROS in normal tissues, and may explain the elevated levels of ROS during the tumor development (Beckman and Ames, 1997).…”
Section: Resultssupporting
confidence: 81%
“…Somatic mutations were classified as point mutations, deletions, or insertions according to previous studies (Li and Hong, 2012;Yu, 2012). The spectrum of somatic mtDNA mutations in common primary human malignancies and other diseases were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Clearly, a defective respiratory chain results in mitochondrial ROS release, which not only contributes to triggering of a NF-jB/AP-1-mediated response but may also lead to a vicious cycle of oxidationinduced mutations of mtDNA/nDNA and chromosomal instability (Li and Hong 2012). To this end, it is striking that a high statistical association was observed between mitochondrial disorders and lymphoid malignancies (Mende et al 2007) and that leukemias are among cancers in which mitochondrial dysfunctions and mtDNA mutations are most common (e.g., He et al 2003;Linnartz et al 2004;Piccoli et al 2008;Schildgen et al 2011;Yao et al 2007).…”
Section: Cancermentioning
confidence: 99%
“…Apoptosis reduction promote the tumorigenesis and tumor progress [29]. TUNEL method was used to analyze the effect of HGF and PKG II on apoptosis of AGS and HGC-27 cells.…”
Section: Resultsmentioning
confidence: 99%